The 'Double-Reduction' Education Policy in China: Three Prevailing Narratives - Qian, Haiyan; Walker, Allan; Chen, Shuangye (Journal of education policy, 2024)
In July 2021 the Chinese Government unexpectedly released what has become known colloquially as the 'Double-Reduction' policy. The policy decreed the reduction of homework pressure on students and greater control of private tutorial companies. In this paper, we set out to understand why the Chinese central government launched the 'Double-Reduction' policy in mid−2021 by using narratives to analyse the three most circulated explanations for the policy and its timing. We use data from a range of formal and informal policy texts. The three narratives, including one policy narrative dominant in the official discourse and two alternative ones, constructed the causal stories about the policy's rationale from multiple perspectives. The combination of multiple perspectives and a narrative approach helps reveal the policy event's complexity and lays a foundation for researchers interested in tracking the development trajectory of this new policy.